2020
DOI: 10.1016/j.diabet.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Associations between specific plasma ceramides and severity of coronary-artery stenosis assessed by coronary angiography

Abstract: Aim: Recent prospective studies have identified distinct plasma ceramides as strong predictors of major adverse cardiovascular events in patients with established or suspected coronary artery disease (CAD). Currently, it is uncertain whether higher levels of distinct plasma ceramides are also associated with greater angiographic severity of coronary-artery stenoses in this patient population. Methods: We measured six previously identified high-risk plasma ceramide species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
0
25
0
3
Order By: Relevance
“…For the first time that the association between high level of Cer (d18:0/24:1)/ Cer (d18:0/24:0) ratio and more severe coronary artery stenosis is reported, and there was no association between any specific ceramide and severity of coronary artery stenosis found in the present study. Recently, Mantovani and colleagues [29] reported that a higher level of plasma Cer (d18:1/24:0), but not Cer (d18:0/24:1), was associated with a greater severity of LAD stenosis after adjustment for cardiovascular risk factors. However, Cer (d18:0/24:1)/Cer (d18:0/24:0) ratio was not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time that the association between high level of Cer (d18:0/24:1)/ Cer (d18:0/24:0) ratio and more severe coronary artery stenosis is reported, and there was no association between any specific ceramide and severity of coronary artery stenosis found in the present study. Recently, Mantovani and colleagues [29] reported that a higher level of plasma Cer (d18:1/24:0), but not Cer (d18:0/24:1), was associated with a greater severity of LAD stenosis after adjustment for cardiovascular risk factors. However, Cer (d18:0/24:1)/Cer (d18:0/24:0) ratio was not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fat induces more pronounced increases in intrahepatic triglyceride content and insulin resistance compared to unsaturated fat and simple sugars [51]. Plasma lipids might also be disease relevant as shown for certain ceramides which concentrations were independently associated with greater severity of coronary artery stenosis in the left anterior descending artery [52]. Mitochondrial dysfunction and endoplasmic reticulum stress activation are also key factors contributing to NAFLD and insulin resistance [53].…”
Section: Multiple Sources Of Cytokines Drive Liver Inflammation and Ementioning
confidence: 99%
“…1,3,4 Large prospective studies have recently identified plasma ceramides with long and very-long chains [mostly increased plasma levels of Cer(d18:1/16:0), Cer(d18:1/18:0), and Cer (d18:1/24:1) and their ratios with Cer(d18:1/24:0)] as significant predictors of cardiovascular morbidity and mortality both in the general population 5 and in patients with established coronary artery disease (CAD) or acute coronary syndrome, independent of traditional cardiovascular risk factors. [6][7][8][9] Additionally, higher levels of these plasma ceramides have been strongly associated with greater angiographic severity of coronary stenoses in patients with CAD, 10 as well as with lower post-stress myocardial wall perfusion in patients with established, or suspected, CAD undergoing stress myocardial perfusion scintigraphy. 11 That said, in this hypothesis-generating study, we have supposed that there is a significant association between higher plasma levels of specific ceramides (that have been previously associated with higher risk of adverse cardiovascular outcomes in patients with CAD) and the risk of cardiovascular mortality also in patients with chronic heart failure (HF), that is, a progressive, complex clinical syndrome characterized by high rates of cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Large prospective studies have recently identified plasma ceramides with long and very‐long chains [mostly increased plasma levels of Cer(d18:1/16:0), Cer(d18:1/18:0), and Cer(d18:1/24:1) and their ratios with Cer(d18:1/24:0)] as significant predictors of cardiovascular morbidity and mortality both in the general population 5 and in patients with established coronary artery disease (CAD) or acute coronary syndrome, independent of traditional cardiovascular risk factors 6–9 . Additionally, higher levels of these plasma ceramides have been strongly associated with greater angiographic severity of coronary stenoses in patients with CAD, 10 as well as with lower post‐stress myocardial wall perfusion in patients with established, or suspected, CAD undergoing stress myocardial perfusion scintigraphy 11 …”
Section: Introductionmentioning
confidence: 99%